Investigations of milk-fat lamb production practices for Western Kansas, Results for 1962-63 creep-feeding tests and 1963 ewe preflushing and flushing tests - Menzies, C.S.; Banbury, Evans E. (Kansas Agricultural Experiment Station, 2011)
One hundred fifty yearling ewes were added to the flock in May, 1963, so the ewe flock now consists of approximately 450 two-, five-, and six- year-old fine-wool ewes. All were purchased in southwestern Texas as yearlings. Purebred Hampshire rams were used.
Keywords: Sheep; Performance; Gain; Flushing